Multidiscip Cancer Investig 2019
DOI: 10.30699/acadpub.mci.3.4.25
|View full text |Cite
|
Sign up to set email alerts
|

In vitroAnticancer Evaluation of Saponins Obtained From Spirulina platensis on MDA, HepG2, and MCF7 Cell Lines

Abstract: Introduction: Microalgae are known for their bioactive compounds with potential applications as antimicrobial, antiaging, and anticancer activities. Spirulina platensis (S. platensis) is a filamentous and photosynthetic microorganism that has 25 kinds of vitamins and minerals that contain many compounds with biotic activity such as alkaloids, phenolic compounds, terpenoids, and saponins. Saponins are mainly present in plants; while there are few studies about their role in microalgae. This study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The cells were cultured in RPMI-1640 medium composed of 10% Fetal Bovine Serum (FBS) (Gibco, USA), and 1% penicillin–streptomycin (Gibco, USA). The cultures were incubated at 37 °C in a CO 2 incubator (Memmert, Germany), under anaerobic incubation of 5% CO 2 , as explained by Akbarizare et al ( 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in RPMI-1640 medium composed of 10% Fetal Bovine Serum (FBS) (Gibco, USA), and 1% penicillin–streptomycin (Gibco, USA). The cultures were incubated at 37 °C in a CO 2 incubator (Memmert, Germany), under anaerobic incubation of 5% CO 2 , as explained by Akbarizare et al ( 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results of antioxidant determinations turned out to be strongly correlated with the total content of phenols [Hadžifejzović et al 2013 There are various methods of saponin extraction. Akbarizare et al (2019) extracted saponins from Spirulina platensis using distilled water and n-butanol. The result showed that saponins from Spirulina decrease cancer cellular viability, and these compounds can be a candidate for anticancer agents.…”
mentioning
confidence: 99%